2020
DOI: 10.1093/infdis/jiaa704
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Reduced-Dose Monovalent Type 2 Oral Poliovirus Vaccine in Mocuba, Mozambique

Abstract: Background Monovalent type 2 oral poliovirus vaccine (mOPV2) stockpile is low. One potential strategy to stretch the existing mOPV2 supply is to administer a reduced dose: one-drop instead of two-drops. Methods We conducted a randomized, controlled, open-label, non-inferiority trial (10% margin) to compared immunogenicity following administration of one versus two-drops of mOPV2. We enrolled 9-22-months old infants from Mocub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…A trial conducted in inactivated poliovirus vaccine vaccinated infants aged 11–18 months in Mozambique showed a type 2 seroconversion rate of 83 (60·6%) of 137 (95% CI 52·2–68·4) following two mOPV2 doses. 22 This finding contrasts with a seroconversion rate of 88 (92%) of 96 (95% CI 84–96) in historic control infants following one dose of mOPV2 in the study in Panama. 10 Thus, the immunogenicity of nOPV2 in this trial is consistent with data for mOPV2 from comparable settings in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 63%
“…A trial conducted in inactivated poliovirus vaccine vaccinated infants aged 11–18 months in Mozambique showed a type 2 seroconversion rate of 83 (60·6%) of 137 (95% CI 52·2–68·4) following two mOPV2 doses. 22 This finding contrasts with a seroconversion rate of 88 (92%) of 96 (95% CI 84–96) in historic control infants following one dose of mOPV2 in the study in Panama. 10 Thus, the immunogenicity of nOPV2 in this trial is consistent with data for mOPV2 from comparable settings in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 63%
“…Type 2 population immunity from OPV (OPV2) declined from a population-weighted median of 87% (IQR 81−93) of children under 5 years in January-June, 2016, to 14% (9-37) in January-June, 2020. In provinces where no mOPV2 has been used, median population immunity from trivalent OPV declined from 88% (IQR 83−92) in children under 5 years in January-June, 2016 to 10% (7)(8)(9)(10)(11)(12)(13)(14) in January-June, 2020 (figure 1). In provinces with mOPV2 use in the past 2 years, median OPV2 immunity was 70% (IQR 49−86).…”
Section: Resultsmentioning
confidence: 99%
“…To estimate per-dose OPV effectiveness, we used data on seroconversion after administration of trivalent OPV or mOPV2 from 38 studies across Africa and Asia, collected in a systematic review conducted in 2018. 9 , 10 , 11 , 12 , 13…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from field use and clinical trials support the hypothesis that nOPV2 would have similar immunogenicity and effectiveness to OPV2. Although findings of reduced immunogenicity of nOPV2 in young children when co-administered with bOPV indicated that nOPV2 may be less robust to competition with other enteroviruses in the gut [ 23 ], a study in the Gambia demonstrated excellent seroconversion in infants and young children (63% post-dose 1 in infants seronegative at baseline [n = 499], 65% in children [n = 66]), at levels comparable to those observed in an mOPV2 trial in a similar setting in Mozambique (68% in children seronegative at baseline [n = 75]) [ 10 , 24 ]. In addition, two in-depth studies comparing mOPV2 and nOPV2 effectiveness in Nigeria, which experienced a large cVDPV2 outbreak in 2021 and used the most nOPV2 of any country, found no significant difference between the two vaccines used in outbreak response campaigns [ 19 , 20 ].…”
Section: Assessment Of Vaccine Effectivenessmentioning
confidence: 99%